2021
DOI: 10.1002/apj.2629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coating structure of granulated quasi‐fuel particles in iron ore sintering

Abstract: To reduce greenhouse gas emissions, biomass fuels are used to gradually replace fossil fuels in the sintering process. Unfortunately, the sinter quality will deteriorate sharply due to too fast combustion rate when using biomass fuels. To address this problem, pregranulation proved to be an effective method. In this study, the pilot‐scale sinter pot tests were carried out to study the effect of coating structure of granulated quasi‐fuel particles on the granulation properties, flame front propagation in sinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The coke breeze and biomass char used are consistent with the materials used in our previous research, as shown in Tables 1 and 2. 29 The ores, fuels, and hydrated lime used are fine powders of less than 250 μm after grinding and screening, the chemical composition of which is shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The coke breeze and biomass char used are consistent with the materials used in our previous research, as shown in Tables 1 and 2. 29 The ores, fuels, and hydrated lime used are fine powders of less than 250 μm after grinding and screening, the chemical composition of which is shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The contact angle between coke breeze and water was significantly larger than that between iron ore and water, which was the main reason for the hydrophobicity of fuel during the granulation process 85) . For the granulation performance of biomass fuels, extensive results have shown that the average particle size of the mixture decreases after the replacement of coke breeze by biomass fuels [86][87][88] , and due to the larger specific surface area and porosity, biomass fuels require more water to be added during granulation compared to coke breeze and anthracite.…”
Section: 12: Fuel and Fluxesmentioning
confidence: 99%
“…It is worth mentioning that when sintering with biomass fuels, processes that use biomass fuels as the core with other feedstock coating are proposed to solve the problems of insufficient liquid phase generation and low productivity caused by the fast combustion rate of biomass fuels 88,119) . The specific step is to pre-granulate the biomass fuel with the flux for 4 minutes, and then add other materials as a coating to wrap the biomass fuel and continue granulation for 4 minutes, as shown in Fig.…”
Section: 32: Coating Addition Of Fuel and Fluxmentioning
confidence: 99%
“…Ji et al used the pregranulation method to encapsulate CaO and magnetite around the fuel, and the experimental results showed that this method slowed charcoal combustion while achieving NOx reduction. Lai et al also demonstrated in their experiments that charcoal coating sintering can reduce the flame front speed, increase the highest bed temperature, and alleviate the decline in sinter quality and output. However, the pregranulation for charcoal is relatively simple, which results in an unsatisfactory coating effect of flux or ore powder on charcoal.…”
Section: Introductionmentioning
confidence: 99%